Influences of Injection Pressure and Flow Rate to the Green Properties - Koon Tatt, Tan; Muhamad, Norhamidi; Hassan Che Haron, Che; Rijal Jamaludin, Khairur (International Journal of Engineering and Technology, 2019)
Injection moulding is one of the essential processes in Metal injection moulding (MIM). The injection pressure and flow rate are the key factors that influence the quality of the MIM parts. In the present study, experimental work has been performed to identify the influence of injection pressure and flow rate to the surface defects, density and the strength of the green parts. Feedstocks used were water atomised stainless steel powder with a solid loading of 62 %vol and the multicomponent binder consisting PEG, PMMA and strearic acid. Tensile specimens were injection moulded by varying injection pressure from 550 bar to 750 bar and flow rate from 10 cm3/s to 20 cm3/s.Â All feedstocks prepared exhibits a shear thinning behaviour. The results show that the green density and green strength decreases as injection pressure increased. The flow rate is directly proportional to the green strength while the green density is unable to correlate with the flow rate. Excess flashing and severe binder separations were observed when the specimens were injection moulded at injection pressure 750 bar and flow rate 20 cm3/s.Â Â